The Concept of Multicultural Education in Enhancing the Tolerance of Santri (Case Study at Ngalah Islamic Boarding School, Pasuruan) - Dilla Rafida Rizqya; Wahidmurni; Alfin Mustikawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the concept, implementation, and impact of multicultural education in improving the tolerance of students at the Ngalah Islamic Boarding School, Pasuruan. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observations, and documentation studies. The subjects of the study included the caretakers of the Islamic boarding school, academics, administrators, and students. Data analysis was carried out through the stages of data condensation, empirical presentation, and verification of conclusions. The results of the study indicate that the concept of multicultural education in improving the tolerance of students includes three main ideas: upholding humanitarian values, respecting diversity, and upholding justice. The implementation of this concept is carried out through bandongan recitation activities, non-discriminatory Islamic boarding school activities, equalizing room placement, and the exemplary behavior of the Kyai. The positive impacts include students having an attitude of mutual respect, mutual cooperation, the ability to face challenges, and an understanding of diverse cultures. However, the negative impacts include a tendency to be neutral without a firm attitude and the division of students' focus from Islamic boarding school teachings. This study is expected to provide insight into the importance of multicultural education in producing tolerant students and supporting unity in diversity.